Voltage-induced fluorescence lifetime imaging of a BODIPY derivative in giant unilamellar vesicles as potential neuron membrane mimics. Issue 94 (11th November 2021) - Sirbu, Dumitru; Zeng, Lingli; Waddell, Paul G.; Tkachenko, Nikolai V.; Botchway, Stanley W.; Benniston, Andrew C.
Abstract : Voltage induced lifetime imaging (VILI) is described using a BODIPY dye and Giant Unilamellar Vesicles (GUVs) as neuron membrane mimics. Fluorescence lifetime modulation was shown to map to a change in voltage across the GUV. Abstract : Fluorescence lifetime imaging (FLIM) was used to study the behaviour of a BODIPY dye in a giant unilamellar vesicle (GUV) in the presence of an electric field. The modulation of the electric field resulted in distinctive fluorescence lifetime changes in line with environment alterations within the membrane mimic.